PENGGUNAAN TEORI-TEORI SOSIAL SEBAGAI ALAT ANALISIS PENELITIAN INTERPRETIF - Parmitasari, Rika Dwi Ayu (Jurnal Minds: Manajemen Ide dan Inspirasi, 2015)
Qualitative method has brought new perspective in research and academic world. One of qualitative method is interpretative approach. Interpretative paradigm includes many sociologists and philosophises that share general characteristics in understanding and explaining social world. Furthermore, this paradigm also motivates scholars to explore social world from people who involves directly in social process. Interpretative approach consists of many approaches. Some of them are ethnography, ethomethodology and phenomenology. Ethnography means a writing or report in terms of anthropology. Ethnomethodology is a knowledge collection based on healthy minds and procedures in order to make society understood and acted based on situation. Lastly, phenomenology is a philosophy that implicates moral value from observation, data collection and conclusion phase.